2004
DOI: 10.1093/nar/gkh191
|View full text |Cite
|
Sign up to set email alerts
|

A primordial RNA modification enzyme: the case of tRNA (m1A) methyltransferase

Abstract: The modified nucleoside 1-methyladenosine (m(1)A) is found in the T-loop of many tRNAs from organisms belonging to the three domains of life (Eukaryota, Bacteria, Archaea). In the T-loop of eukaryotic and bacterial tRNAs, m(1)A is present at position 58, whereas in archaeal tRNAs it is present at position(s) 58 and/or 57, m(1)A57 being the obligatory intermediate in the biosynthesis of 1-methylinosine (m(1)I57). In yeast, the formation of m(1)A58 is catalysed by the essential tRNA (m(1)A58) methyltransferase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
118
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 45 publications
3
118
0
Order By: Relevance
“…Although m 1 A58 in the T loop of tRNA has also been shown to be essential for the viability of yeast (Anderson et al 2000), due to its role in maintaining steady-state levels of eukaryotic initiator tRNA (Anderson et al 1998), it is not uniformly present in human cells (Saikia et al 2010) and is rare in bacteria, indicating that it is not a broad-based antimicrobial target. Also, while m 1 A58 is synthesized by the TrmI enzyme in bacteria (Roovers et al 2004;Varshney et al 2004) but by a Trm6-Trm61 complex in eukaryotes (Anderson et al 1998), the bacterial TrmI shares homology with the eukaryotic Trm61, indicating an orthologous relationship between the two enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Although m 1 A58 in the T loop of tRNA has also been shown to be essential for the viability of yeast (Anderson et al 2000), due to its role in maintaining steady-state levels of eukaryotic initiator tRNA (Anderson et al 1998), it is not uniformly present in human cells (Saikia et al 2010) and is rare in bacteria, indicating that it is not a broad-based antimicrobial target. Also, while m 1 A58 is synthesized by the TrmI enzyme in bacteria (Roovers et al 2004;Varshney et al 2004) but by a Trm6-Trm61 complex in eukaryotes (Anderson et al 1998), the bacterial TrmI shares homology with the eukaryotic Trm61, indicating an orthologous relationship between the two enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…6 This hypothesis was demonstrated experimentally for the bacterial orthologs in Thermus thermophilus and Mycobacterium tuberculosis and for the archaeal ortholog in Pyrococcus abyssi. 3,[7][8][9] These proteins are α 4 homotetramers of Trm61p-like proteins, hereafter called TrmI. Interestingly, orthologs of the Trm6p protein could only be found in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with the conventional nomenclature of tRNA modification enzymes from yeast, GCD10 and GCD14 are now referred to as TRM6 and TRM61, respectively (Kadaba et al 2004). While structural and functional homologs of Trm61p have been identified in Archaea and Eubacteria (Bujnicki 2001;Gupta et al 2001;Droogmans et al 2003;Roovers et al 2004;Varshney et al 2004), homologs of Trm6p have not been found in the sequenced genomes of organisms 1 Present address: The College of St. Scholastica, Duluth, MN 55811, USA.…”
Section: Introductionmentioning
confidence: 99%